# Step-by-step Solution

## Solve the equation $1-\left(\frac{2u-3}{4}\right)=\frac{2-5u}{3}-3u$

Go!
Go!
1
2
3
4
5
6
7
8
9
0
a
b
c
d
f
g
m
n
u
v
w
x
y
z
.
(◻)
+
-
×
◻/◻
/
÷
2

e
π
ln
log
log
lim
d/dx
Dx
|◻|
θ
=
>
<
>=
<=
sin
cos
tan
cot
sec
csc

asin
acos
atan
acot
asec
acsc

sinh
cosh
tanh
coth
sech
csch

asinh
acosh
atanh
acoth
asech
acsch

### Videos

$u=-\frac{13}{50}$

## Step-by-step Solution

Problem to solve:

$1-\frac{2u-3}{4}=\frac{2-5u}{3}-3u$

Choose the solving method

1

Take $\frac{-1}{4}$ out of the fraction

$1-\frac{1}{4}\left(2u-3\right)=\frac{2-5u}{3}-3u$

Learn how to solve equations problems step by step online.

$1-\frac{1}{4}\left(2u-3\right)=\frac{2-5u}{3}-3u$

Learn how to solve equations problems step by step online. Solve the equation 1-(2u-3)/4=(2-5u)/3-3u. Take \frac{-1}{4} out of the fraction. Multiply the single term -\frac{1}{4} by each term of the polynomial \left(2u-3\right). Add the values 1 and \frac{3}{4}. Combine all terms into a single fraction with 3 as common denominator.

$u=-\frac{13}{50}$
SnapXam A2

### beta Got another answer? Verify it!

Go!
1
2
3
4
5
6
7
8
9
0
a
b
c
d
f
g
m
n
u
v
w
x
y
z
.
(◻)
+
-
×
◻/◻
/
÷
2

e
π
ln
log
log
lim
d/dx
Dx
|◻|
θ
=
>
<
>=
<=
sin
cos
tan
cot
sec
csc

asin
acos
atan
acot
asec
acsc

sinh
cosh
tanh
coth
sech
csch

asinh
acosh
atanh
acoth
asech
acsch

$1-\frac{2u-3}{4}=\frac{2-5u}{3}-3u$